Case histories of intense pulsed light phototherapy in dermatology - the HPPL™ and IFL™ technologies - Alessandro Martella; Mauro Raichi (PAGEPress Publications, 2017)
The intense pulsed light (IPL) and laser technologies are widely used for skin rejuvenation and for treating several dermatological disorders such as skin dyschromia and acne, and for non-ablative dermal remodeling of rhytides and hypertrophic scars. Technological evolution is rapid. The High Power Pulsed Light™ [HPPL™] and Incoherent Fast Light™ technologies [IFL™, Novavision Group S.p.A., 20826 Misinto (MB), Italy] are recent innovations in the field of IPL technologies; IFL™ is a further evolution of the already advanced HPPL™ system. The paper presents a selection of case histories of dermatological lesions treated with the HPPL™ and IFL™ technologies. All study materials were appropriately peer-reviewed for ethical problems.